2019
DOI: 10.2109/jcersj2.18131
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and microstructure of CuFeO<sub>2</sub> powders via microwave hydrothermal reaction

Abstract: The CuFeO 2 powders have been synthesized by the microwave hydrothermal reaction at different reaction temperatures. The pure rhombohedral phase for CuFeO 2 has been formed and confirmed by the X-ray diffraction (XRD). The microstructure and morphology for all CuFeO 2 samples have been scanned by the Transmission Electronic Microscope (TEM). Various scales of grains for powders have been found spanning from several nanometers to hundreds of nanometers, and even few scales are over 1¯m for some grains. The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Then, the powders were treated in Argon flow at 573 K for 2 h and then spark plasma sintered under 40 MPa axial pressure at 623 K for 5 min to give the highest ZT of 0.82. Zhai et al [39] found that the grain growth in CuFeO2 powders synthesized by the microwave hydrothermal (MH) reaction satisfied the theory of classical Ostwald ripening, and a pure rhombohedral phase in the material has been formed, as shown in Figure 1e. Nanostructured particles of size in the range 50-100 nm were formed in Ga-doped ZnO made by the MH technique [40].…”
Section: Microwave-assisted Solvothermal/hydrothermal Synthesismentioning
confidence: 79%
See 2 more Smart Citations
“…Then, the powders were treated in Argon flow at 573 K for 2 h and then spark plasma sintered under 40 MPa axial pressure at 623 K for 5 min to give the highest ZT of 0.82. Zhai et al [39] found that the grain growth in CuFeO2 powders synthesized by the microwave hydrothermal (MH) reaction satisfied the theory of classical Ostwald ripening, and a pure rhombohedral phase in the material has been formed, as shown in Figure 1e. Nanostructured particles of size in the range 50-100 nm were formed in Ga-doped ZnO made by the MH technique [40].…”
Section: Microwave-assisted Solvothermal/hydrothermal Synthesismentioning
confidence: 79%
“…Point defects in Zr, Sn, or Hf, Sn co-doped Cu 3 SbSe 4 nanoparticles can be seen in Figure 1 g. Then, the powders were treated in Argon flow at 573 K for 2 h and then spark plasma sintered under 40 MPa axial pressure at 623 K for 5 min to give the highest ZT of 0.82. Zhai et al [ 39 ] found that the grain growth in CuFeO2 powders synthesized by the microwave hydrothermal (MH) reaction satisfied the theory of classical Ostwald ripening, and a pure rhombohedral phase in the material has been formed, as shown in Figure 1 e. Nanostructured particles of size in the range 50–100 nm were formed in Ga-doped ZnO made by the MH technique [ 40 ]. A one-step MH procedure was used to prepare phase-pure polycrystalline Sn 1- δ S with a high ZT of 0.76 at 523 K due to relatively good mobility and high carrier concentration [ 41 ].…”
Section: Various Synthesis and Fabrication Techniques For Large-scale Productionmentioning
confidence: 99%
See 1 more Smart Citation